Linguoculturological description of the spatial code of culture (based on the material of the Russian and Tuvan languages) - Vorobyev , Vladimir V.; Fatkullina , Fluza G.; Kuzhuget, Shenne Yu. (The New Research of Tuva, 2023)
The article delves into a specific segment of the linguistic worldview shared by the Russian and Tuvan ethnic groups. This exploration centers on the analysis of phraseological and paremiological units that are intricately linked to the concept of space. The study meticulously discerns the distinct mental frameworks and perceptual paradigms prevalent in these ethnic groups. This discernment is facilitated through a meticulous examination of these linguistic units, viewed as symbolic representations embedded within the cultural language. The research endeavor is focused on unearthing culturally significant meanings inherent in the semantics of the scrutinized units, while taking into account their nuanced figurative connotations. The linguocultural analysis of the examined linguistic code is constructed upon the identification of culturally significant information. This involves establishing correlations between the spatial code and the broader cultural code. The study meticulously dissects the mechanisms, resemblances, and disparities underpinning the formation and operation of this specific cultural code. Emphasis is placed on exploring semantic oppositions, or models, such as own/foreign, up/down, and near/far. These oppositions, which prove to be universal across both languages, harbor diverse potentials in the linguocultural and figurative representation of spatial relationships.